AMICUS CURIAE AS THE DEVELOPMENT OF EVIDENCE IN CRIMINAL PROCEDURE CODE - Dwi Herman Sucipta; I Made Wirya Darma (Faculty of Law Universitas Padjadjaran, 2022)
Article 184 paragraph (1) of the Criminal Procedure Code has limitedly determined legal evidence according to the law, however, in the last few years, the Indonesian Court of Justice has emerged Amicus Curiae. In this study, it will be discussed the legal basis for judges to apply the Amicus Curiae as evidence of a crime in positive law in Indonesia today (ius constitutum) then the second issue will discuss the Amicus Curiae as evidence development in the KUHAP in the future come (ius constituendum). The research method used is normative juridical or library research related to normative legal substances, to find the truth based on scientific logic from the normative side by examining library materials or secondary data consisting of primary and secondary legal materials. Amicus Curiae is a legal concept that is not well known in Indonesia which adheres to the Civil Law legal system. The legal concept of Amicus Curiae is indeed only practiced in the traditions of countries that adhere to the common law legal system. The proof using the Amicus Curiae concept has been found in many cases in Indonesia. However, legally the Amicus Curiae has not been regulated in positive law in Indonesia.